Ultra-Broadband Bending Beam and Bottle Beam Based on Acoustic Metamaterials - Xudong Fan; Xiaolong Huang; Yang Kang; Can Li; Ning Li; Chunsheng Weng (Applied Sciences, 2022)
We report the realization of an ultra-broadband bending beam based on acoustic metamaterials by the theoretical prediction and the numerical validation. The proposed structure is composed of a series of straight tubes with spatially modulated depths. We analytically derive the depth profile required for the generation of an ultra-broadband bending beam, and examine the performance of the metastructure numerically. The design is then extended for the generation of a three-dimensional bottle beam. The transverse trapping behaviours on small rigid objects by the bottle beam are investigated based on the force potential. Our work will help the further study of broadband acoustic meta-structures, and may also find applications in a variety of fields such as ultrasound imaging, health monitoring and particle manipulations.